POTRET KELOMPOK REMAJA PENGGEMAR SEPEDA FIXIE DI BANDAR LAMPUNG - Herinda, Nisa; Damayantie, Anita (SOCIOLOGIE, 2013)
The objective of this research is to analyze the reasons why a person joins the fixie bicycle teenager group, to analyze activities of the fixie bicycle teenager group in Bandar Lampung, and to analyze effects of joining the fixie bicycle teenager group. This was a qualitative research focusing to the reasons why a person joins the After Skool fixie bicycle teenager group, activities of After Skool, and effects of joining After Skool fixie bicycle teenager group. Data were collected from deep interviews with informants and literary study. Informants were 5 members of After Skool who were suitable with determined criteria. Informants were selected based ont their knowledge about conditions and activities of fixie bicycle teenager group, duration of joining the group, routine levels, and education levels. Data were analyzed qualitatively using data reduction, data display and data verification.Â The results showed various reasons of After Skool members in joining the fixie bicycle teenager group. Fixie bicycle as a life style recently attracted teenager interests especially those who loved bicycle. It was a particular proud for the member to join the group. When a teenager drove a unique and âcoolâ fixie bicycle,he/she felt to be âfashionedâ and âcoolâ. Activities of After Skool group were not only bicycling, but After Skool group also committed social service activities. The effects were not only the members got healthy, but their social sensitivity also increased.Keywords: Images, group, teen, fan fixie bike